Analysis of adhesion formation of a new elastic thermoplastic polyurethane (TPU) mesh in comparison to polypropylene (PP) meshes in IPOM position. (January 2016) - Lambertz, A.; Hil, L.v.d.; Schöb, D.S.; Binnebösel, M.; Kroh, A.; Klinge, U.; Neumann, U.P.; Klink, C.D.
Abstract: Background: Postsurgical adhesions severely affect the patients' quality of life causing various complications like bowel obstruction or chronic pain. Especially the implantation of alloplastic prostheses in IPOM position for hernia repair carries a high risk of adhesion formation due to the close contact between mesh and viscera. The extent of adhesions mainly depends on the type and textile characteristics of the implanted mesh. The aim of this study was to examine the degree of adhesion formation of a newly developed, elastic thermoplastic polyurethane (TPU) mesh in comparison to polypropylene (PP) meshes in IPOM position in a rabbit model. Methods: Sixteen female chinchilla rabbits were laparoscopically operated. Two different meshes were placed to the left and the right lower abdominal wall in IPOM position in each rabbit. After 7 or 21 days, midline laparotomy was performed, the degree of adhesion formation was examined by the Diamond score and mesh elongation was measured under a force of 3 N. Finally, the abdominal walls were explanted for immunohistochemical and histopathological investigations. Results: TPU meshes showed significantly lower Diamond scores than PP meshes. After explantation, mesh elongation of the TPU mesh was significantly larger than expansion of PP under a force of 3 N. Thus, the TPU mesh preserved its elastic properties after 7 and 21 days. The amount of CD68 positive, Ki67 positive and apoptotic cells within the granuloma around the fibers did not show significant differences between the study groups. Conclusions: The newly developed TPU mesh seems to reduce peritoneal adhesion formation in IPOM position in a rabbit model compared to PP meshes after 7 and 21 days. Immunohistochemistry did not reveal differences in biocompatibility of the two meshes used. Highlights: An elastic TPU mesh seems to reduce peritoneal adhesion formation in IPOM position. The TPU mesh preserved its elastic properties after 7 and 21 days. Immunohistochemistry did not reveal differences in biocompatibility.